Commentary on 'Competence in chronic mental illness: the relevance of practical wisdom' - Crisp, R (BMJ Publishing Group, 2016)
As this interesting paper well brings out, the assessment of competence to make decisions can be especially difficult in cases of adult mental illness. The paper revolves around two such cases, both involving OCD. Jack realises his symptoms are peculiar, but resists admission to a psychiatric unit because he prefers not changing his way of life. Later, deep brain stimulation is of some therapeutic benefit, but he is now considering discontinuing treatment. Mary decides to stop treatment based on anti-depressants and CBT, and later, on the advice of her psychiatrist, becomes involved in childcare, which provides some health benefits.